Fenitrothion induced oxidative stress and morphological alterations of sperm and testes in male sprague-dawley rats (Clinics, 2013)
OBJECTIVE: Fenitrothion residue is found primarily in soil, water and food products and can lead to a variety of toxic effects on the immune, hepatobiliary and hematological systems. However, the effects of fenitrothion on the male reproductive system remain unclear. This study aimed to evaluate the effects of fenitrothion on the sperm and testes of male Sprague-Dawley rats. METHODS: A 20 mg/kg dose of fenitrothion was administered orally by gavages for 28 consecutive days. Blood sample was obtained by cardiac puncture and dissection of the testes and cauda epididymis was performed to obtain sperm. The effects of fenitrothion on the body and organ weight, biochemical and oxidative stress, sperm characteristics, histology and ultrastructural changes in the testes were evaluated. RESULTS: Fenitrothion significantly decreased the body weight gain and weight of the epididymis compared with the control group. Fenitrothion also decreased plasma cholinesterase activity compared with the control group. Fenitrothion altered the sperm characteristics, such as sperm concentration, sperm viability and normal sperm morphology, compared with the control group. Oxidative stress markers, such as malondialdehyde, protein carbonyl, total glutathione and glutathione S-transferase, were significantly increased and superoxide dismutase activity was significantly decreased in the fenitrothion-treated group compared with the control group. The histopathological and ultrastructural examination of the testes of the fenitrothion-treated group revealed alterations corresponding with the biochemical changes compared with the control group. CONCLUSION: A 20 mg/kg dose of fenitrothion caused deleterious effects on the sperm and testes of Sprague-Dawley rats.